Double-Skin Facades: Advantages, Disadvantages, and Design Considerations - Eman Ali Al-Awag; Izudinshah Abd Wahab (Techniques and Innovation in Engineering Research Vol. 9, 2023)
Double-skin facades (DSF) have been widely used in modern building design due to their potential to improve energy efficiency and indoor comfort while enhancing aesthetics. Despite that, there is an ongoing debate about the advantages and disadvantages of DSF due to the limited availability of reliable data on their actual performance. Therefore, this study aims to provide a comprehensive overview of the advantages and disadvantages of DSF systems by reviewing previous studies investigating the benefits and limitations of using the DSF system based on different parameters, namely, the DSF components and types. The results indicate that appropriately designed DSF systems can positively impact building performance and the environment by reducing energy consumption and improving thermal comfort. However, the high maintenance and construction costs of DSF systems remain a challenge that needs to be addressed in future research.